Онтогенез видів роду Bidens L. долини Середнього Дніпра - Makhinya, L.M. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2011)
Data about ontogeny of annual species Bidens L. (Asteraceae), that are met in the valley of the Middle Dniepre are presented. The characteristic of 4 age periods and 7 age states are given. The prospects of further investigation on onyogeny of this genus species are enlightened.